放電加工によるTi3AlC2 セラミックスの機械的性質の変化に関する一考察 - 品田, 健陽; 南口, 誠; 金子, 健正; 郭, 妍伶; 山口, 直也 (電気加工学会誌, 2023)
The effects of electrical discharge machining on the mechanical properties of MAX phase ceramics were investigated. Wire electrical discharge machining was performed on Ti3AlC2, a MAX phase ceramics, as a workpiece in deionized water or working oil. Mechanical properties were evaluated on the basis of the Vickers hardness and 3-point bending strength of the electrical discharge machined surface. The Vickers hardness and bending strength were increased by electrical discharge machining in both working fluids. The cross-sectional observation of the machined surface by SEM showed that cracks were generated from the machined surface to the base material. In addition, the formation of a recast layer with a thickness of a few micro meters was observed on the machined surface. The elemental analysis of the machined surface by EDS revealed the presence of oxygen in deionized water machining. Furthermore, the ratio of Ti to Al changed in both working fluids. The component identification of the recast layer by XRD revealed peaks of Al2O3 and TiC, which have higher mechanical properties than the base material.